Indexing at Latindex and article very well received by the scientific community. - Coelho Paraguassu, Eber (Brazilian Journal of Implantology and Health Sciences, 2020)
Dear readers and collaborators of BJIHS, it was with great joy that we received the news of the indexing of our newspaper in the largest and most important database in Latin America, Latindex. Although it does not require presentations, Latindex (Regional Online Information System for Scientific Journals in Latin America, the Caribbean, Spain and Portugal) initially called the Latin American Index of Serial Scientific Publications, is an academic, non-profit and consultation information system free of charge, specialized in scientific journals produced in Ibero-American countries, as a result of cooperation between different institutions in 23 countries; it also offers information on thematic journals on Latin America published outside the region. Another good news was the metric scope of the article “COVID-19, health system disaster in the present and economic tragedy in the very near future. ”¹ by authors Pedro Lemos, Naomar Almeida-Filho and Josélia Firmo [1]. The article in question in just one month already has 4 citations in Google Scholar and we believe that very soon it will be responsible for raising our H index to 6. We are very grateful to all the authors who publish with us and make each issue this journal much more relevant within the academic community of health sciences.